Acquirer Internal Control Weaknesses in the Market for Corporate Control - Darrough, Masako; Huang, Rong; Zur, Emanuel (Contemporary Accounting Research, 2018)
Abstract This paper examines how disclosures regarding internal controls, required by sections 302 and 404 of the Sarbanes‐Oxley Act of 2002 ( SOX ), affect the market for corporate control. We hypothesize that acquirers with internal control weaknesses ( ICW s) make suboptimal acquisition decisions based on poor‐quality information generated by their ineffective controls over financial reporting. We expect that such acquirers will be more likely to misestimate the value of their targets or the potential synergies from mergers, thereby overpaying for completed deals. Using a treatment sample of acquisitions made by acquirers that have disclosed ICW s and two matched control samples without ICW disclosures, we document that ICW acquirers experience a substantially more negative market response to acquisition announcements and have lower future performance than the two matched control samples without ICW disclosures. Overall, our results suggest that ineffective internal controls hinder decision making related to mergers and acquisitions (M&A).